From Sonic Models to Sonic Hooligans: Magnetic Tape and the Unraveling of the Mao-Era Sound Regime, 1958–1983. Issue 3 (1st September 2019) - Xu, Chuan
Abstract: This article examines the roles of magnetic recording in China's sound governance. Through analyses of archival documents and personal accounts, this article argues that in the early 1980s, the magnetic recording infrastructure and its common usage underwent dramatic transformations. In the 1960s and 1970s, state officials and language educators configured the magnetic recording infrastructure to propagandize authoritative and normative sounds while maintaining strict hierarchical distinctions between those who recorded and those who listened. In the early 1980s, with the rapid popularization of compact cassettes and recorders, these distinctions dissolved as millions of people began to produce and exchange dubbed cassettes. Widespread home dubbing created a decentralized network of sound production and circulation that not only defied government regulation, but also fueled the anxieties that moral, social, and ideological catastrophes would soon descend on the country. Through this media history of magnetic tape, this article shows how the governance of sound infrastructure and protocols was integral to the governance of people.